Agriculture land markets in transition - The inherited challenge of the post-communist land reform in Albania. (August 2021) - Zhllima, Edvin; Rama, Klodjan; Imami, Drini
Abstract: Land consolidation has been viewed by policy makers as a panacea for tackling the inherited challenges of Albania´s egalitarian land reform. This paper argues that farmers´ efforts towards farm consolidation through land purchase and rent-in are affected by farm structure, farm-orientation and other socio-economic factors. The form of land acquisition is another important factor affecting land transaction, and is related to tenure security in that the origin of ownership is perceived as more important than formal land titles for many households. In the context of existing agriculture conditions, the rental market has been the most common mechanism for farm consolidation, despite land renting not being considered suitable for agriculture activities that require long term investments. Highlights: The paper analyses the dysfunctional land market of a transition economy dominated by small farms. The origin of ownership is perceived as more important than formal land titles for many households. Farm consolidation through land purchase and rent-in is affected by farm structure, farm-orientation and socio-economic factors. The rental market is the most common form for farm consolidation as land purchases have been affected by tenure insecurity.